Work From Home (WFH) dan Pembentukan Kecerdasan Moral Anak di Era Pandemi Covid 19 - Mayana Ratih Permatasari (Wahana Islamika: Jurnal Studi Keislaman, 2020)
This study aims to critically analize the impact of work from home on the formation of children’s moral inteligence during the covid 19 pandemic. This research is library research because it explores more of the contents and concepts contained in books. The research method used is descriptive analytical method. In general, the impact of work from home on the formation of children’s moral intelligence can be divided into two, namely negative and positive impacts. A negative impact occurs when parents fail to interact and care for and educate the children with good moral intelligence because they have burdened with a lot of office work. While the positive impact occur when parents succeed in playing their role as educators, caregivers an mentors of children during work from home properly.